2013
DOI: 10.1177/0333102413505237
|View full text |Cite
|
Sign up to set email alerts
|

Sturge-Weber syndrome with late onset hemiplegic migraine-like attacks and progressive unilateral cerebral atrophy

Abstract: We propose to consider SWS as a cause of apparently isolated hemiplegic migraine and lamotrigine as a preventive medication in HM-like attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
16
0
3
Order By: Relevance
“…We identified 7 cases of symptomatic HM: 3 patients with SWS and 1 patient with Moyamoya disease, CREST syndrome, PAVM, and systemic lupus erythematosus (SLE; Table ) . Each of the diseases shows evidence of vascular dysfunction, including both systemic and CNS vascular disorders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 7 cases of symptomatic HM: 3 patients with SWS and 1 patient with Moyamoya disease, CREST syndrome, PAVM, and systemic lupus erythematosus (SLE; Table ) . Each of the diseases shows evidence of vascular dysfunction, including both systemic and CNS vascular disorders.…”
Section: Resultsmentioning
confidence: 99%
“…As we perform our literature review regarding symptomatic HM, we find that vascular‐related theory is more substantiated by cases. (See Tables and ) Diseases including SWS, CREST syndrome, PAVM, Moyamoya disease, and SLE are prevalent causes of HM. Although these patients had no characteristic age at onset, sex, headache side, headache duration, weakness side or weakness duration, and frequency, they all show vascular abnormalities to various degrees, including both central and systemic blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Although it is challenging to appreciate the complete FDG-PET findings without a thorough analysis of the data, it appears that the axial map provided in Fig 2A of that report could suggest marked hypometabolism associated with the DVA in the right cerebellum relative to the homologous contralateral region. In another case report, Planche et al 21 described a patient with a DVA and cortical hypometabolism demonstrated on FDG-PET, though this finding was confounded by superimposed pathology of Sturge-Weber syndrome, including extensive pial angiomatosis. Brain metabolism has been previously evaluated by using FDG-PET in patients with cavernous malformations.…”
Section: Figmentioning
confidence: 99%
“…In one case of Sturge‐Weber syndrome who had refractory headache associated with aura‐like manifestations, a remarkable improvement was reported under LTG at 25 mg/day . In another individual, escalation of LTG dose up to 200 mg/day prevented the occurrence of repeated and long‐lasting hemiplegic aura‐like manifestations . These manifestations with a long progression of aura symptoms appear clearly distinct from ictal headache commonly misdiagnosed as MA .…”
Section: Accumulating Evidence Suggests That Lamotrigine May Reduce Tmentioning
confidence: 97%